Analisis Dinamika Perkembangan Hukum Pasar Modal di Indonesia - Aridah, Naily; Haikal, Rewidan Muhammad (Anthology: Inside Intellectual Property Rights, 2025)
The development of the capital market in Indonesia has shown a significant impact on the nation’s economic growth. This development has gone through a long history since the Dutch colonial era. This study aims to examine and analyze the development of capital market law in Indonesia which is dynamic in the context of history, legal basis, and dispute resolution. This study uses a normative legal method with a qualitative approach. The results of the study show that the capital market in Indonesia has gone through approximately 9 dynamic phases that play an important role in the Indonesian economy, in addition, disputes in the capital market realm can be resolved through non-litigation with the assistance of BAPMI and litigation based on civil and criminal law with the help of law enforcement officers.